EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VII MTs AL ICHSAN NANGGULAN - Pramana, Sigit; Ningsih, Siska Candra (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2023)
This study aims to determine the effectiveness of the use of the Scramble type cooperative learning model on theability to understand mathematical concepts of seventh grade students at MTs Al Ichsan Nanggulan. This research wasconducted at MTs Al Ichsan Nanggulan in the 2021/2022 academic year. This type of research is a quasi-experimentalresearch with Posttest Only Control Design. In this study the sampling technique used is simple random sampling. Fromthe four population classes, two sample classes were taken, namely class VII C as the experimental class and class VIID as the control class. The instruments used in this study were observation sheets and tests. Technical analysis of thedata in this study is to use the normality test and homogeneity test as well as hypothesis testing. The results of the posttestnormality test of the experimental class obtained the value of sig. 0.152 0.05 and in the control class the sig value wasobtained. 0.200 0.05, so the post-test scores of both classes were normally distributed. The homogeneity test of theposttest value obtained the value of sig. 0.153 0.05, so the variance of the two classes is homogeneous. Furthermore,because the prerequisite test is met, a t-test is carried out. The results of the first hypothesis test were obtained, namely16.26 2.04523, which means that the Scramble-type cooperative learning model is effective on the ability to understandmathematical concepts of seventh grade students at Mts Al Ichsan Nanggulan. The results of the second hypothesis testwere obtained, namely 4.59 2.04523, which means that the conventional learning model is effective on the ability tounderstand mathematical concepts of seventh grade students at Mts Al Ichsan Nanggulan. The results of the thirdhypothesis test are obtained, namely 7.901 2.001, which means that the Scramble type cooperative learning model ismore effective than the conventional learning model on the ability to understand mathematical concepts of seventh gradestudents at Mts Al Ichsan Nanggulan..Keywords: math learning;Scramble learning model;understanding of mathematical concepts